Urban Mobility Choices of University Students: Insights into Satisfaction Levels and Preferences in the Thessaloniki Metropolitan Area - Efstathios Bouhouras; Thomas Dimos; Dimitrios Mastoras; Socrates Basbas (Urban Science)
Assessing people’s satisfaction with diverse modes of transportation is complex yet crucial. This paper delves into the pivotal outcomes derived from analyzing survey data. The surveys, conducted at Aristotle University of Thessaloniki (AUTH), gauged student satisfaction with the available transport options in the Thessaloniki Metropolitan Area during 2021 and 2022, thus providing insights into trends in satisfaction levels, allowing for a deeper understanding of evolving mobility preferences. Through a comparative analysis of the data, we discerned attributes influencing participants’ transportation choices. Our research contributes to the literature by applying a standardized methodology using an algorithm developed by the European Commission; the satisfaction levels among university students for private car and public transport in those years were determined. Notably, the findings underscore that, despite a marginally higher usage of public transport, university students exhibit a greater satisfaction level with private car transportation. This implies a nuanced preference for private car usage among students, as opposed to a mere emphasis on the higher popularity of public transport within this demographic. The findings aim to provide transport operators and policymakers with valuable information in terms of ways to enhance sustainable urban mobility and improve public transport services.